Strengthening Africa's capacity for vaccine research: Needs and challenges - Adedoyin John-Joy Owolade; Taiwo Oluwaseun Sokunbi; Favour Oluwatobi Aremu; Esther Oluwatosin Omotosho; Blessing Abai Sunday; Yusuff Adebayo Adebisi; Aniekan Ekpenyong; Abdulhammed Opeyemi Babatunde (Tabriz University of Medical Sciences, 2022)
Vaccine development and production harbinger the control and eradication of infectious diseases. Vaccination played a huge role in the curtailment of disease outbreaks like smallpox and polio, especially in Africa. Despite the high demand for several vaccines in Africa due to the highly infectious disease burden, the continent still lacks adequate capacity for vaccine research and development. This paper aims to discuss the need and challenges of Africa to strengthen its capacity for vaccine research and development and also highlight practical recommendations. Some of the needs for Africa to prioritize vaccine research and development include; improving quality of life and well-being, cost-effectiveness, independent preparedness and response to local outbreaks, and increased access to funding. Challenges associated with vaccine research and development include the cost of the investment, risk of failure; poor ethical framework and legislation; lack of adequate funding; lack of political will & support; and poor surveillance system. Strategies to create sufficient research funds, an efficient surveillance system, and a legislative framework are clearly described. In conclusion, strengthening vaccine research capacity in Africa requires the political goodwill of African governments and strategic partnerships with international organizations and institutes. The challenges facing this development and possible solutions have been highlighted in this article.